2023
DOI: 10.1021/acs.inorgchem.2c03678
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Dependent Self-Assembly of a Pillar[5]arene-Based Poly-Pseudo-Rotaxane Linked and Threaded by Silver(I) Trifluoroacetate: A Double Role

Abstract: In the supramolecule area, the fabrication of a new concept called polyrotaxanes or poly-pseudo-rotaxanes remains challenging. We herein report the formation of a poly-pseudo-rotaxane in which the same salt-type guest serves both linking and threading in the resulting structure. The combination of A1/A2-thiopyridyl pillar[5]arene (L) and silver(I) trifluoroacetate in CHCl 3 /CH 3 OH afforded a one-dimensional (1D) poly-pseudo-rotaxane. In this structure, to our surprise, the AgCF 3 CO 2 guest not only links th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Since the solvent has a significant influence on the hierarchically chiral self-assembly of TPP-Chol, other organic solvents were also investigated in detail. ,, After a systematical investigation of TPP-Chol in various solvents, we found that TPP-Chol with the concentration of 5 × 10 –3 mol/L formed a transparent solution in chloroform but viscous solution in hexane, toluene, and p -xylene, and suspension in other solvents including 1,2-dichloroethane (DCE), tetrahydrofuran (THF), ethyl acetate (EA), dodecanol (12-OH), acetone, and methanol, etc. The self-assembly behavior of TPP-Chol in these solvents was further investigated by the CD measurements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the solvent has a significant influence on the hierarchically chiral self-assembly of TPP-Chol, other organic solvents were also investigated in detail. ,, After a systematical investigation of TPP-Chol in various solvents, we found that TPP-Chol with the concentration of 5 × 10 –3 mol/L formed a transparent solution in chloroform but viscous solution in hexane, toluene, and p -xylene, and suspension in other solvents including 1,2-dichloroethane (DCE), tetrahydrofuran (THF), ethyl acetate (EA), dodecanol (12-OH), acetone, and methanol, etc. The self-assembly behavior of TPP-Chol in these solvents was further investigated by the CD measurements.…”
Section: Resultsmentioning
confidence: 99%
“…In artificial self-assembly systems, the chiral molecular building blocks can be collectively driven by the hydrogen-bonding, π–π stacking, metal–ligand coordination and other noncovalent interactions, thereby resulting in various hierarchical chirality expressions for the resultant supramolecular polymers . The expression of hierarchical chirality plays a crucial role in determining the structures of chiral supramolecular materials and endows them with dynamic and smart functions. The challenge is how to achieve the assembled nanostructures with chirality at different scales through the hierarchical self-assembly, due to the high complexity and tunable mutability affected by solvent, assembly pathway, and other external stimuli in solution assembly systems. In the recent years, we have developed a series of cholesterol-based building blocks to construct the metal-organic supramolecular polymers with dynamic supramolecular chirality regulation, including chirality amplification, helix-to-superhelix transformation and handedness inversion .…”
Section: Introductionmentioning
confidence: 99%